Reactive Extraction of Jatropha curcas L. Seed for Production of Biodiesel: Process Optimization Study - Shuit, Siew Hoong (American Chemical Society, 2010)
Biodiesel from Jatropha curcas L. seed is conventionally produced via a two-step method: extraction of oil and subsequent esterification/transesterification to fatty acid methyl esters (FAME), commonly known as biodiesel. Contrarily, in this study, a single step in situ extraction, esterification and transesterification (collectively known as reactive extraction) of J. curcas L. seed to biodiesel, was investigated and optimized. Design of experiments (DOE) was used to study the effect of various process parametersonthe yield ofFAME.Theprocess parameters studied include reaction temperature (30-60 °C), methanol to seed ratio (5-20 mL/g), catalyst loading (5-30 wt %), and reaction time (1-24 h). The optimum reaction condition was then obtained by using response surface methodology (RSM) coupled with central composite design (CCD). Results showed that an optimum biodiesel yield of 98.1% can be obtained under the following reaction conditions: reaction temperature of 60 °C, methanol to seed ratio of 10.5 mL/g, 21.8 wt % of H2SO4, and reaction period of 10 h.